Butterfly Hug Therapy: Pelatihan Bagi Ibu dengan Inner Child Negatif - Harahap, Ade Chita Putri; Harahap, Dinda Permatasari; Simarmata, Sari Wardani; Armitasari , Armitasari (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2025)
Mental health is a crucial aspect of an individual's overall well-being. Untreated mental health conditions, particularly unresolved past trauma or issues related to the "inner child," can significantly influence a person's current behavior and attitudes. The inner child refers to the part of the self that retains emotional experiences from childhood, including unfulfilled joys and unmet needs, which continue to impact adult life. Contributing factors to the development of the inner child include family environment, parent-child relationships, and early emotional experiences. A wounded inner child may manifest through symptoms such as frustration, exaggerated emotional reactions, childish outbursts, difficulty in expressing emotions, low self-esteem, immaturity, and fear of abandonment. This community service activity aimed to provide training for mothers experiencing high levels of negative inner child symptoms through the implementation of Butterfly Hug Therapy. Participants were selected based on their elevated negative inner child scores. The training involved both theoretical sessions and practical exercises in Butterfly Hug Therapy, which consists of crossing the arms over the chest and gently tapping the shoulders alternately. This self-soothing technique helps individuals achieve a sense of safety, allowing them to process emotional experiences effectively. Previous studies have demonstrated that Butterfly Hug Therapy can reduce anxiety levels across age groups, enhance self-awareness, and strengthen emotional regulation. The results of this program indicated a significant reduction in negative inner child symptoms among the participating mothers. These findings suggest that Butterfly Hug Therapy is an effective, non-pharmacological intervention for addressing unresolved childhood emotional issues. The therapy promotes emotional regulation and cognitive processing by stimulating brain regions associated with perception, evaluation, and emotional control, ultimately reducing psychological stress.